1996
DOI: 10.1007/bf03011769
|View full text |Cite
|
Sign up to set email alerts
|

High-dose thiopentone for open-chamber cardiac surgery: a retrospective review

Abstract: Purpose: High-dose

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…However, further studies of the use of thiopental were not quite as positive. A study by Pascoe et al (5) and one by Zaidan et al (6) failed to support a beneficial effect of thiopental on neurologic outcome after cardiac surgery. These negative trials coupled with the side effects of prolonged sedation tempered the optimism for barbiturates.…”
Section: Pharmacologic Neuroprotective Drugsmentioning
confidence: 97%
“…However, further studies of the use of thiopental were not quite as positive. A study by Pascoe et al (5) and one by Zaidan et al (6) failed to support a beneficial effect of thiopental on neurologic outcome after cardiac surgery. These negative trials coupled with the side effects of prolonged sedation tempered the optimism for barbiturates.…”
Section: Pharmacologic Neuroprotective Drugsmentioning
confidence: 97%
“…Recently, a retrospective evaluation of 227 open-heart surgery patients showed that thiopental (an average of 38.1 mg•kg -1 ) had no beneficial effect on neurological outcome. 11 (b) Propofol Propofol has been shown to have a similar effect as thiopental on CMRO 2 . In addition, many recent studies have shown propofol to be effective against focal cerebral ischemia, oxidative stress or glutamate toxicity in both in vitro and in vivo animal experiments.…”
Section: (B) Nmda Antagonistsmentioning
confidence: 99%
“…Recently, a retrospective evaluation of 227 open-heart surgery patients showed that thiopental (an average of 38.1 mg·kg −1 ) had no beneficial effect on neurological outcome. 11…”
Section: Introductionmentioning
confidence: 99%
“…A recent retrospective review by Pascoe et al also found no benefit of thiopentone in open-chamber cardiac surgery. 36 The evidence, therefore, suggests that thiopentone has little neuroprotective effect.…”
Section: Thiopentonementioning
confidence: 99%